Les ‘Ulamā’ et la propriété foncière en Ifrīqiya (Ier-IIIe/VIIe-IXe siècles) - Tahar Mansouri (Revue des Mondes Musulmans et de la Méditerranée)
The biographic sources (kutub al-tarāğim), which deal with the history of Ifrīqiya give us a great number of biographies of pious men. Through those texts we can find scarce information about the rural and agronomic implication of this category of people. Our contribution doesn’t deal with wealth of these men, but about their rural wealth. This situation allows seeing the constitution of the rural property of men of knowledge and the rural law or farmer’s law.In fine we can say that the muslim civilisation is not based only on the urban economy as it was usually suggested, but also, the rural wealth is important and the better example is the example of ‘Ulamā’ and their rural wealth.